Shallow and deep groundwater moderate methane dynamics in a high Arctic glacial catchment - Kleber, Gabrielle Emma; Magerl, Leonard; Turchyn, Alexandra V.; Redeker, Kelly; Thiele, Stefan; Liira, Martin; Herodes, Koit; Øvreas, Lise; Hodson, Andrew (Frontiers in Earth Science, 2024)
Glacial groundwater can mobilize deep-seated methane from beneath glaciers and permafrost in the Arctic, leading to atmospheric emissions of this greenhouse gas. We present a temporal, hydro-chemical dataset of methane-rich groundwater collected during two melt seasons from a high Arctic glacial forefield to explore the seasonal dynamics of methane emissions. We use methane and ion concentrations and the isotopic composition of water and methane to investigate the sources of groundwater and the origin of the methane that the groundwater transports to the surface. Our results suggest two sources of groundwater, one shallow and one deep, which mix, and moderate methane dynamics. During summer, deep methane-rich groundwater is diluted by shallow oxygenated groundwater, leading to some microbial methane oxidation prior to its emergence at the surface. Characterization of the microbial compositions in the groundwater shows that microbial activity is an important seasonal methane sink along this flow-path. In the groundwater pool studied, we found that potential methane emissions were reduced by an average of 29% (±14%) throughout the summer due to microbial oxidation. During winter, deep groundwater remains active while many shallow systems shut down due to freezing, reducing subsurface methane oxidation, and potentially permitting larger methane emissions. Our results suggest that ratios of the different groundwater sources will change in the future as aquifer capacities and recharge volumes increase in a warming climate.